Temperature-Controlled Diastereoselective Doebner/Ugi Tandem Reaction - Sakhno, Yana; Radchenko, Oleksandr; Saraev, Vyacheslav; Shliapkina, Yuliia; Kaidash, Mariia; Shyshkina, Mariia; Shishkina, Svitlana; Musatov, Vladimir; Desenko, Sergey; Chebanov, Valentyn (SynOpen, 2023)
Novel peptidomimetics containing a pyrrolone fragment were synthesized by a tandem combination of Doebner and Ugi type multicomponent reactions with controlled diastereoselectivity. This approach represents a convenient synthesis in the temperature range from 25 to 45 °C. In most cases, the new method allowed each diastereomer to be isolated separately.
Keywords: multicomponent reactions; Doebner reaction; Ugi reaction; peptidomimetics; pyrrolones; diastereoselectivity